Pencapaian Keunggulan Bersaing Melalui Inovasi Produk, Kualitas Produk dan Kualitas Pelayanan pada Kedai Kopi di Kota Bandung - Muhammad Haviel Nurachman (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purpose of this study was to determine the achievement of competitive advantage through product innovation, product quality, and service quality at coffee shops in Bandung. The analytical method used is descriptive analysis and verification with a quantitative approach. The test tool used is multiple regression analysis. Using questionnaires and interviews about competitive advantage through product innovation, product quality and service quality as a means of collecting data with coffee shop owner respondents. The results of descriptive research which show that the Competitive Advantage at Coffee Shops in Bandung is in the poor category, the product innovation that has been done is still not good, the product quality given is still not good, the service quality that has been provided is quite optimal. Furthermore, the results of verification research show that Product Innovation, Product Quality and Service Quality have a significant effect on Competitive Advantage either partially or simultaneously. Product Innovation Variable is the variable that has the most dominant influence on Competitive Advantage.